RELIGIOUS AND AXIOLOGICAL ISSUES AND HUMAN LIFE ACTIVITY - Шавріна, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted the analysis of the existent going near correlation of values and religion in life of man and society. The methodological problems of functioning of the system of values in society and forming of morality of man are examined.